Public-Private Collaboration for Productive Development Policies in Colombia (2013)
This study analyzes the institutions that shape public private collaboration for the design and implementation of productive development policies in Colombia. Colombia is an interesting case because productive development policies are increasingly designed, in principle, in the context of formal institutions and venues, with public-private collaboration being a pillar of that formal design. We focus on two specific cases: (1) the Private Council for Competitiveness and its role in the National System for Competitiveness; (2) the Colombian government¿s Productive Transformation Program. These case studies suggest that public private collaboration has contributed to the continuity of productive development policies across governments. Collaboration has also been behind particular achievements, such as helping overcome specific government failures, and helping develop private organizational capabilities. A central message of this document is thus that formal institutions to foster public private collaboration, such as the ones adopted in Colombia over the last few decades, have an important potential for advancing adequate productive development policies. However, public private collaboration for productive policies has by no means brought a development ¿miracle¿.